TrkA serves as a virulence modulator in Porphyromonas gingivalis by maintaining heme acquisition and pathogenesis - Zou, Renjie; Zhao, Lei; Shen, Daonan; Wu, Yafei (Frontiers in Cellular and Infection Microbiology, 2022)
Periodontitis is an inflammatory disease of the supporting tissues of teeth, with polymicrobial infection serving as the major pathogenic factor. As the periodontitis related keystone pathogen, Porphyromonas gingivalis can orchestrate polymicrobial biofilm skewing into dysbiosis. Some metatranscriptomic researches have suggested modulation of potassium ion uptake might serve as a signal enhancing microbiota nososymbiocity and periodontitis progression. Despite the relationship between potassium transport and virulence has been elucidated in some bacteria, less is mentioned in periodontitis-related pathogen. Herein, we centered on the virulence modulation potential of TrkA, sole potassium uptake regulatory protein of P. gingivalis, and uncovered TrkA as the modulator in heme acquisition process and maintaining optimal pathogenicity in experimental murine model of periodontitis. The hemagglutination and hemolytic activities were attenuated in the case of trkA gene loss. And entire transcriptomic profiling revealed trkA gene can control the expression of genes in relation to electron transport chain activity and translation, as well as some transcriptional factors, including cdhR, the regulator of heme uptake system hmuYR. Collectively, these results link the heme acquisition process to potassium transporter, providing a new insight into the role of potassium ion in P. gingivalis pathogenesis.